The Influence of the Fundamental Factors on Plantation Companies’ Firm Value on the Indonesia Stock Exchange - Siska Gita Pratiwi; Robiyanto Robiyanto; Harijono Harijono (Journal of Management and Entrepreneurship Research, 2020)
Objective: Indonesia’s economic growth is mostly supported by the agricultural sector in which the plantation sub-sector has a significant contribution to the primary sector in the sectoral index of Indonesia Stock Exchange (IDX). Plantation companies have a long-term goal of maximizing shareholder prosperity by increasing company values. This study aimed to determine the influence of fundamental factors on company values of plantation companies listed on the IDX during 2015-2019. Research Design & Methods: This study used secondary data involving 8 samples of plantation companies listed on the IDX using a purposive sampling method and panel regression analysis techniques. Research data was taken from the annual reports on the IDX. Findings: The results showed that Managerial Ownership (MO), Debt to Equity Ratio (DER), Earnings per Share (EPS), and Company Age (AGE) have a positive correlation to Firm Value (FV). However, the probability of MO, EPS, AGE is not significant and only DER has a significant effect on FV. Recommendations: There is a blemish in research for further research that is expanding the scope of research, and future studies is suggested to analyze the fundamental influence on FV before and during the Covid-19 period. This cannot be done in this study because the data is still limited. Contribution & Value Added: This result contributes to the financial literature and can be a consideration for investors in investment based on company value.